Pelatihan Pembuatan Furniture Minimalis Dengan Teknik Finishing Ramah Lingkungan Pada Kelompok Karang Taruna Bina Gapura - Fahrussiam, Fauzan; Nurul Chaerani; Dini Lestari; Andrie Ridzki Prasetyo; Hassyati Shabrina; Musdi; Fadli; Eka Nurminda Dewi Mandalika (Universitas Mataram, 2024)
The issue of unemployment in West Nusa Tenggara (NTB), particularly among the youth, has prompted skill-training initiatives aimed at enhancing productivity and community empowerment. This community service project was conducted with the Bina Gapura Youth Organization in Perina Village, Central Lombok, with the goal of training participants in producing minimalist furniture using the environmentally friendly yakisugi finishing technique. This technique is known for its efficiency, aesthetic appeal, and ability to improve wood durability against destructive organisms without the use of harmful chemicals. The training method included foundational material on wood characteristics, practical application of the yakisugi finishing technique, and an introduction to woodworking machinery. Participants were also provided guidance in business strategy formulation through the Business Model Canvas (BMC) as an initial management framework for business development. The results indicate that participants developed a sound understanding of the yakisugi finishing process, as evidenced by the aesthetically pleasing wooden products created during the practical sessions. Collaborative processes with small and medium enterprises (SMEs) in wood processing are expected to greatly assist in the initial stages of business development